2018
DOI: 10.1111/pirs.12242
|View full text |Cite
|
Sign up to set email alerts
|

Do economic crises lead tourists to closer destinations? Italy at the time of the Great Recession

Abstract: This article studies how distance influences the choice of tourists about their holiday destination during times of economic crisis. In particular, we analyse the specific case of domestic tourism flows across Italian regions during the 2000–2012 period by estimating a gravity model. Our estimations yield the effect of distance year by year. The output suggests that distance gained weight during the years of the Great Recession and therefore confirms, from a macroeconomic perspective, that tourists tend to cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 50 publications
2
29
1
Order By: Relevance
“…However, other variables have been included to take into account the common attributes considered to be relevant determinants of tourism demand. In line with traditional gravity model, we adopt a measure of distance between origin and destination proxying geographical or physical but also intangible measures of distance, hypothesized to play a discouraging role on tourist flows (for a comprehensive overview of the role of distance in tourism flows see, for instance, Cafiso, Cellini, & Cuccia, 2018). The variable has been calculated as the distance between European countries centroids and each European NUTS 2 region centroid and measured in kilometres.…”
Section: Data and Model Descriptionmentioning
confidence: 99%
“…However, other variables have been included to take into account the common attributes considered to be relevant determinants of tourism demand. In line with traditional gravity model, we adopt a measure of distance between origin and destination proxying geographical or physical but also intangible measures of distance, hypothesized to play a discouraging role on tourist flows (for a comprehensive overview of the role of distance in tourism flows see, for instance, Cafiso, Cellini, & Cuccia, 2018). The variable has been calculated as the distance between European countries centroids and each European NUTS 2 region centroid and measured in kilometres.…”
Section: Data and Model Descriptionmentioning
confidence: 99%
“…This crisis, which reached Europe in 2008, has had important negative consequences on the economies of European countries. In the context of the tourism industry, the literature has analysed the impact of this crisis of in Cyprus (Boukas and Ziakas, 2013), Greece (Magoutas, Papadoudis and Sfakianakis, 2018), Italy (Cafiso, Cellini, and Cuccia, 2018) and Spain (García López, Campoy Muñoz, Cardenete Flores and Marchena Gómez, 2018).…”
Section: Economic Crisis and Tourism Sectormentioning
confidence: 99%
“…Cafiso, Cellini, and Cuccia () estimated the destination choices of travelers during the Great Recession based on geographic distances. They found the gaining importance of geographic distance between origin and tourism destination during a recessionary period and confirmed that tourists prefer closer destinations to the ones over longer distances.…”
Section: Literature Reviewmentioning
confidence: 99%